PENGARUH KEBERADAAN KAMPUS TERHADAP PERUBAHAN FISIK KAWASAN DI SEKITARNYA (STUDI KASUS: KAWASAN BABARSARI, KECAMATAN DEPOK, YOGYAKARTA) - Tutik Rahayu Ningsih (Diponegoro University, 2017)
Yogyakarta is a city known as the city of education. The potential of education in Yogyakarta is not only recognized by the local community, but also by people throughout Indonesia. The identity makes the city of Yogyakarta as an educational city much in demand in the city, outside the city and even the foreign community. Campus as a forum for the wider community in gaining knowledge can be a new growth center that causes changes to the surrounding area. In the Babarsari region there are several campuses that trigger the development of the surrounding area. Babarsari region became a crowded area considering that every year hundreds of students come from various regions to gain knowledge and settle in this area. In addition to the students, this opportunity is used by communities or migrants from other places to settle and make business in the area around the campus. Seeing the potential that exists, people urbanize into the Babarsari region, so the Babarsari region is more dense as a result of population growth. The development of the area in Babarsari fosters the use of new lands that are utilized as supporting facilities for campus existence. Babarsari is one of the areas of education centers that experienced rapid development of the region. This causes an impact on the population growth followed by increasing the density of the building so that in the end there is a physical change of the surrounding area. This study aims to identify the extent of physical changes in the area that occurred in the region Babarsari. In this research using qualitative descriptive method supported by quantitative data analysis. Quantitative analysis is done through the approach of figure ground analysis and land use analysis.The results showed that the physical changes of the area since 2003-2017 ie the use of agricultural land turned into a wake land of 4% per 7 years.